Formation of the principle of legal certainty in the legal positions of the Constitutional Court of Ukraine (On the example of decisions of the Constitutional Court of Ukraine for the period from 1996 to 2005) - Bogatiuk, Oksana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
Research on the formation of approaches to understanding and applying the principle of legal certainty as an element of the rule of law in the legal positions of the Constitutional Court of Ukraine for the period from 1996 to 2005. The conclusion about the approaches of the Constitutional Court of Ukraine on this issue is made. Examining the activities of the Constitutional Court of Ukraine in the period from 1996 to 2005, it can be noted that the Constitutional Court of Ukraine in its acts and legal positions does not give a clear definition of the principle of legal certainty.At the same time, the formation of the approaches of the Constitutional Court of Ukraine to the application of the principle of legal certainty is carried out through the definition of its components.The main components of the principles of legal certainty, the formation and development of which are reflected in the legal positions of the Constitutional Court of Ukraine for the above period are: stability, predictability, legality (unambiguity and accuracy of legal norms), prohibition of retroactive effect of law, unambiguous legal regulation and accuracy interpretation of the rule of law.